2022
DOI: 10.30868/ad.v6i01.2287
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Konversi Bank BUMD Menjadi Bank Syariah Implikasinya Pada Peningkatan Market Share Bank Syariah di Indonesia (Studi Kasus Bank Aceh Syariah dan Bank NTB Syariah)

Abstract: This paper describes descriptively and analytically related to the conversion of BUMD Banks into Islamic Banks. The banks in question are Bank Aceh Syariah and Bank NTB Syariah. These two banks are proven to have contributed significantly in increasing the market share of Islamic banks in Indonesia. The author argues that this conversion pattern is more effective in increasing the market share of Islamic banks, automatically all customers of conventional banks previously became customers of Islamic banks, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Market share, in turn, determines a bank's competitive position relative to its peers (Adenan et al, 2021). Previous studies have consistently shown a significant increase in market share following the full conversion to a Sharia bank (Ribowo & Nurdin, 2022;Al Arif et al, 2023). Prior study shows that Islamic banks have better asset quality and more stable than the conventional banks (Sakti & Mohamad, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Market share, in turn, determines a bank's competitive position relative to its peers (Adenan et al, 2021). Previous studies have consistently shown a significant increase in market share following the full conversion to a Sharia bank (Ribowo & Nurdin, 2022;Al Arif et al, 2023). Prior study shows that Islamic banks have better asset quality and more stable than the conventional banks (Sakti & Mohamad, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Perubahan operasional Bank Aceh dari prinsip konvensional menuju prinsip syariah sesuai keputusan Dewan Kominioner OJK Nomor KEP-44/D.03/2016 tanggal 1 September 2016 perihal pemberian Izin Perubahan Kegiatan Usaha Bank Umum Konvensional menjadi Bank Umum Syariah PT. Bank Aceh, Perubahan ini disambut antusias oleh nasabah bank Aceh (Ribowo & Nurdin, 2022;Ribowo & Nurdin, 2022).…”
Section: Eksistensi Lembaga Keuangan Syariah (Lks) DI Acehunclassified
“…Al, 2022). Disadvantages of bank syariah Limited access: Bank syariah may have limited access compared to bank konvensional, as they may not have as many branches or ATMs also Bank syariah may still be perceived as less established or less trustworthy compared to bank konvensional, as they are a relatively new concept in Indonesia (Ribowo & Nurdin, 2022). There are some respondents who do not know the difference between these two types of banking, this suggests that sharia financial literacy in Indonesia is still very weak and requires more massive sharia financial training or literacy in the future.…”
Section: Advantages and Disadvantages Of Conventional Vs Sharia Bankmentioning
confidence: 99%